QUACS: Routing Data Packets in Ad Hoc Networks on Buffer-Constrained Load Balancing Conditions During Emergency Rescue Crisis - Chengetanai, Gibson; Osunmakinde, Isaac Olusegun (Wireless personal communications, 2018)
Mobile wireless networks have been gaining popularity since the turn of the new millennium as they enable communication to take place without fixed communication infrastructure. This form of communication, which has been made possible by radio links proved its usefulness during emergency medical rescues such as an Ebola pandemic, battlefield communications or other emergency situations, where quick communication is of paramount importance. Nature-inspired algorithms such as AntHocNet, AntSense, among other ant inspired techniques, have been mimicked in solving the communication challenges in wireless networks, but they focus mostly on the ‘next-hop’ in determining routing of data packets from the source to the destination, which tends to suffer from congestion-related problems. Ant routing methods focus more on next-hop neighbours when choosing the shortest path which might have many data packets and are prone to congestion. Focusing on the next-hop neighbours poses a challenge of having other nodes that end up being congested. This problem of routes being heavily used, often decreases throughput rates, leading to the proposed Queuing Ant Colony System (QUACS) which is a bio-inspired, complementing the queuing optimisation approach in routing of data packets across the network. The results of simulations show that QUACS performs better in throughput, packet delivery ratio, end-to-end delay and communication overhead than other ant routing algorithms. This study is particularly beneficial in the ad hoc networks where the QUACS routing method can greatly assist in faster communication and evacuation in emergency for treatment of patients during emergency medical rescue operations.